Extracellular Vesicles from Steatotic Hepatocytes Provoke Pro-Fibrotic Responses in Cultured Stellate Cells - Maria Teresa Koenen; Elisa Fabiana Brandt; Dawid Marcin Kaczor; Tim Caspers; Alexandra Catharina Anna Heinzmann; Petra Fischer; Daniel Heinrichs; Theresa Hildegard Wirtz; Christian Trautwein; Rory R Koenen; Marie-Luise Berres (Biomolecules, 2022)
Hepatic steatosis and chronic hepatocyte damage ultimately lead to liver fibrosis. Key pathophysiological steps are the activation and transdifferentiation of hepatic stellate cells. We assessed the interplay between hepatocytes and hepatic stellate cells under normal and steatotic conditions. We hypothesized that hepatocyte-derived extracellular vesicles (EVs) modify the phenotype of stellate cells. By high speed centrifugation, EVs were isolated from conditioned media of the hepatocellular carcinoma cell line HepG2 under baseline conditions (C-EVs) or after induction of steatosis by linoleic and oleic acids for 24 h (FA-EVs). Migration of the human stellate cell line TWNT4 and of primary human stellate cells towards the respective EVs and sera of MAFLD patients were investigated using Boyden chambers. Phenotype alterations after incubation with EVs were determined by qRT-PCR, Western blotting and immunofluorescence staining. HepG2 cells released more EVs after treatment with fatty acids. Chemotactic migration of TWNT4 and primary hepatic stellate cells was increased, specifically towards FA-EVs. Prolonged incubation of TWNT4 cells with FA-EVs induced expression of proliferation markers and a myofibroblast-like phenotype. Though the expression of the collagen type 1 <semantics>α</semantics>1 gene did not change after FA-EV treatment, expression of the myofibroblast markers, e.g., <semantics>α</semantics>-smooth-muscle-cell actin and TIMP1, was significantly increased. We conclude that EVs from steatotic hepatocytes can influence the behavior, phenotypes and expression levels of remodeling markers of stellate cells and guides their directed migration. These findings imply EVs as operational, intercellular communicators in the pathophysiology of steatosis-associated liver fibrosis and might represent a novel diagnostic parameter and therapeutic target.